2013
DOI: 10.3847/aer2013002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Conceptual Understandings of Citizen Scientists Participating in Zooniverse Projects: A First Approach

Abstract: The Zooniverse projects turn everyday people into "citizen scientists" who work online with real data to assist scientists in conducting research on a variety of topics related to galaxies, exoplanets, lunar craters, and solar flares, among others. This paper describes our initial study to assess the conceptual knowledge and reasoning abilities of citizen scientists participating in two Zooniverse projects: Galaxy Zoo and Moon Zoo. In order to measure their knowledge and abilities, we developed two new assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 16 publications
2
33
0
1
Order By: Relevance
“…Previous work has found a correlation between astronomical content knowledge and length of participation in two Zooniverse Astronomy Projects (Galaxy Zoo and Moon Zoo; Prather et al [2013]). Another study used measures of the change in language of Zooniverse users on "Talk" between the first and last 10% of posts to demonstrate learning [Luczak-Rösch et al, 2014].…”
Section: Introduction To the Zooniversementioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has found a correlation between astronomical content knowledge and length of participation in two Zooniverse Astronomy Projects (Galaxy Zoo and Moon Zoo; Prather et al [2013]). Another study used measures of the change in language of Zooniverse users on "Talk" between the first and last 10% of posts to demonstrate learning [Luczak-Rösch et al, 2014].…”
Section: Introduction To the Zooniversementioning
confidence: 99%
“…Furthermore, science content learning can be shown to take place amongst at least a subset of volunteers in many online projects [e.g. Prather et al, 2013;Luczak-Rösch et al, 2014]. However, these two goals -of education and of scientific productivity -may often be in conflict, with time spent by project organizers furthering one not being spent on furthering the other.…”
mentioning
confidence: 99%
“…Prather et al (2013) offered Galaxy Zoo and Moon Zoo volunteers the opportunity to take questionnaires that tested their understanding of the astrophysics associated with each project and found that performance on this questionnaire correlated with high levels of participation in the projects. In a quantitative analysis of ten of the Zooniverse projects, Luczak-Roesch et al (2014) detected significant shifts toward more advanced vocabulary used on the discussion boards over the lifetime of each project.…”
Section: Motivationmentioning
confidence: 99%
“…17 The well-known European Universe Awareness programme also makes it clear that project goals include the somewhat abstract outcome of changes in intergroup attitudes, but no guidelines as to how these domains might be measured are provided in their evaluation manual. 18 Rather, evaluation tends to be directed solely at the level of astronomy awareness, knowledge, understanding and skills, 19,20 for example, correctly identifying a galaxy (knowledge) or using a telescope (skills). A final example is provided in the evaluation approach of the Sol programme run by NASA for underrepresented communities.…”
Section: Challenges In Evaluating Astronomy Outreach Programmesmentioning
confidence: 99%